Analisa Penerapan Budaya Perilaku Keselamatan dan Kesehatan Kerja di Rumah Sakit - Ardi, Subhan Zul; Hariyono, Widodo (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2018)
Background: Panti Rapih Yogyakarta Hospital is a health institution that organizes health services. Various potential hazards in hospitals due to physical factors, chemical factors, biological factors, ergonomics factors, psychosocial factors, mechanical hazards, electrical hazards, and hospital wastes could lead to illness, and work-related accidents. From the potential hazard in the hospital then did prevention and reduced risk of danger, need a way that was by cultivated behavior of occupational health and safety in hospital (K3RS), at Panti Rapih Hospital has been applied K3RS but still there were workers who did not use Personal Protective Equipment (PPE). The purpose of this study was to analyze the culture of safety behavior after the implementation of occupational safety and health (OSH) at Panti Rapih Hospital. Method: This research was a qualitative research with case study approach. Data collection was conducted by observation and indepth interview. The informants in this research were the Head of P2K3, OSH Secretary, Head of Equipment, equipment staff, and cleaning staff. Results: The result showed Panti Rapih Hospital has already has a program to civilize OSH, among others that was with management commitment with the formation of written policy and stated in vision of mission of hospital accompanied by making of OSH organization, OSH regulation and procedure in every job with formula formulation and procedure by management and safety comitee, communication with safety poster, safety sign, training, competence of worker with OSH general expert and understanding about OSH, worker involvement in the form of training and reporting of accident, and work environment that all employees are actively involved in OSH. Conclusion: The culture of safety behavior in Panti Rapih Hospital has been well implemented supported by written policy, the existence of OHS procedures and regulations, communication between management and employees, worker competence, employee involvement, worker communication, and work environment.